The Influence of Human Resources Audit on Employee Job Satisfaction (A Case Study at PT. Bank Pembangunan Daerah West Java and Banten, Tbk (BJB) Central Office Bandung) - Hawa Az-Zahra Kifayah; Syakieb Arsalan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The main purpose of this paper is to identify how HR audits affected job satisfaction. In this study, 52 participants were surveyed and analyzed using a quantitative descriptive analysis technique. A questionnaire served as the instrument for gathering information, and SPSS 25 was used for analysis, specifically the multiple linear regression technique. The hypothesis that "There is an effect of Human Resources Audit on Employee Job Satisfaction according to hypothesis test on (t test) that is carried out on human resources data, yielding a significance value smaller from the 5% error rate (α = 0,05). The coefficient of determination, also derived based on test result analysis, this suggests a Human Resources Audit contributed to an increase in employee reports of being satisfied with their jobs (by 62.24%). Following the results of both tests it can find out with certainty that in this study the Human Resources Audit is having an effect on Employee Job Satisfaction.